Rheology Charactrization of Drag Reducing Agents - Avazpour, Mahrokh; Abdulbari, Hayder A. (2015)
Transportation of liquids through pipelines is considered as one of the high energy dissipation sources in the industry due to the turbulent flow of transportation [1-4]. Several attempts are spotted in the literatures introducing different techniques to reduce the energy dissipation in pipelines. Generally, these techniques can be classified into two major categories namely, Passive and Active. Mostly, Passive drag reduction techniques uses riblets, dimples, wavy and oscillating walls, compliant surfaces and micro-bubbles and these techniques do not need the additives (5, 6]. Active techniques were the first and most common solution for drag reduction with operation of a minute concentration of an additive or drag reducing agent (DRA) into the transported liquid. A DRA can be generally selected from suspended solids, polymers and surfactants (7-11].